Pengaruh Komunikasi Organisasi, Disiplin Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pabrik Gula Gending Kabupaten Probolinggo - Moch Vishal Fergiawan; Hermanto Hermanto; Trivosa Aprilia Novadiani Haidiputri (Universitas Panca Marga, 2023)
The purpose of the research was to see the influence between the variables of organizational communication, work discipline, and organizational commitment on the performance of employees of the Gending Sugar Factory, Probolinggo Regency. The type of research is quantitative with a causal associative approach. The population came from the AKU office (Administration, Finance and General) totaling 45 people and sampling using non probability sampling and saturated sample method. So the sample was 45 people. Data analysis techniques used validity, reliability, classical assumptions, multiple linear regression analysis, coefficient of determination, and hypothesis testing (t test). The results of hypothesis testing obtained the conclusion that the variables of organizational communication, work discipline and organizational commitment have a positive and significant effect on the performance of employees of the Gending Sugar Factory, Probolinggo Regency.